Relationship between Playing Ability and Motor Fitness Components for Female Volleyball Players from North Karnataka: The impact of playing ability on motor fitness components in female volleyball players (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to find out the effect of varied methods of playing ability on selected motor fitness components of collegiate Female volleyball players. To achieve the purpose of the present study, thirty Female volleyball players were selected as subjects from Karnataka University, Dharwad (Karnataka) and Karnataka Law University, Hubbali, Karnataka during the academic year 2017- 2018. The subjects were selected on a random basis. The ages of subjects were ranged from18-25 years. The collected data were analyzed statistically by using Analysis of Pearson correlations used to determine the difference, test means on selected dependent variables separately. In all the cases, 0.05 level of confidence was fixed to test the level of significance